2015
DOI: 10.1002/prep.201500187
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructuring of Pure and Composite‐Based K6 Formulations with Low Sensitivities

Abstract: The aim of this work was to desensitize keto‐RDX, respectively 2‐oxo‐1,3,5‐trinitro‐1,3,5‐triazacyclohexane (K6). For this purpose, two different methods were employed. First, nano‐K6 was produced by means of the Spray Flash Evaporation process. Particles with a median size of 74 nm were obtained. Sensitivity to friction and electrostatic discharge were reduced by downscaling particle size of K6. Second, due to their molecular analogy, the mixing of K6 and RDX was studied. For that reason, a physical nanometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…It consists in spraying a pressurized low boiling solvent containing the product to be crystallized through a heated hollow cone nozzle, in a vacuum chamber. The sudden pressure and temperature drops induce fast evaporation leading to crystallization of submicrometric [12] to nanometric particles [13]. In our study, ADN is solubilized either in ethyl acetate or in methyl acetate.…”
Section: Experimental Set-upmentioning
confidence: 99%
See 1 more Smart Citation
“…It consists in spraying a pressurized low boiling solvent containing the product to be crystallized through a heated hollow cone nozzle, in a vacuum chamber. The sudden pressure and temperature drops induce fast evaporation leading to crystallization of submicrometric [12] to nanometric particles [13]. In our study, ADN is solubilized either in ethyl acetate or in methyl acetate.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…In 2012, Risse et al [10] introduced the Spray Flash Evaporation (SFE) process to reduce particles size of energetic materials at submicron scale. In this way, recrystallization of pure products like HMX [11], RDX [12], K-6 [13] was achieved with particle sizes of 116 nm, 500 nm and 74 nm respectively. Since then, this process has been extended to drugs [14].…”
Section: Introductionmentioning
confidence: 99%
“…The size reduction is performed by recrystallization on the submicron scale using the Spray Flash Evaporation process. This technology proved its ability to produce submicron explosives and oxidants [34,35] as well as non-energetic organic compounds, co-crystals and diverse composites [36,37]. It is based on the spray of a superheated solution.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable efforts have been made worldwide on reducing the particle size of common explosives and a number of studies have found that submicron-and nano-explosives have much lower impact sensitivity when compared with conventional explosives [4][5][6][7][8][9]. However, some studies have presented opposing results, showing that reducing the particle size increases the impact sensitivity [10][11][12][13][14]. The uncertainty in the bulk density of loose powder samples used in the standard impact sensitivity test was assumed to account for this inconsistency [15].…”
Section: Introductionmentioning
confidence: 99%